Development of problem mind mapping-based learning model (PMM-BL) integration patterns to improve critical thinking skills in primary school students - Ariyanti, Lita; Hanurawan, Fattah; Ramli, M. (Edelweiss Applied Science and Technology, 2024)
PISA 2022 data shows that Indonesia’s ranking has risen 5-6 positions compared to PISA 2018. However, even though there was an increase in ranking in PISA 2022, Indonesia recorded a decrease in scores in each ability assessment subject. Therefore, Indonesia actually still has the opportunity to develop a model (PMM-BL) integration patterns to improve critical thinking skills because it has the capacity and potential that have not yet been developed. The purpose of this research is to produce a PMM-BL model book product and its operational form to improve critical thinking skills and test differences in students’ critical thinking skills before and after implementing the PMM-BL. The research subjects during the limited trial of the PMM-BL model were fifth-grade students at SDN Bandulan 2, Malang City, Indonesia. The research method used is research and development (R&D). The development procedure is guided by the stages of the systems approach model, namely Dick & Cary’s learning system development design model. This study examined the development of the PMM-BL model and its operational form to improve critical thinking skills and examines differences in students’ critical thinking abilities before and after implementing the PMM-BL model.